The Pink Panther strikes again [videorecording (DVD)] - Edwards, Blake, 1922-2010; Sellers, Peter, 1925-1980; Lom, Herbert (MGM Home Entertainment, 2004)
After a nervous breakdown, Chief Inspector Dreyfus builds a criminal organization devoted to the extermination of Inspector Clouseau.